The Democratic Heresy. Maritain’s Impact on Social Magisterium (Cultura Económica, 2019)
The article studies the importance of Jacques Maritain's philosophy in shaping the humanist Christian thinking. The author draws a historical overview, starting in the 1930s in Argentina, when the influence of Catholicism in the country’s social life became consolidated. Bosca also describes how Argentine philosophers, for whom liberal democracy was a heresy threatening the authoritarian order they advocated, received Maritain's philosophy. However, history would eventually confirm the ideas of the French philosopher, during the pontificate of Pius XII, and later in Pope Paul VI's encyclicals. Ultimately, it became one of the foundations of Christian personalism in the pontificate of John Paul II, who notes the profound accordance of the Maritainian thinking with the great project of the Magisterium of the Church.
Keywords: MARITAIN; SOCIAL MAGISTERIUM; CHRISTIAN HUMANISM; CATHOLIC CULTURE; LIBERAL DEMOCRACY